Mitochondrial targeted therapy with elamipretide (MTP-131) as an adjunct to tumor necrosis factor inhibition for traumatic optic neuropathy in the acute setting. (October 2020) - Tse, Brian C.; Dvoriantchikova, Galina; Tao, Wensi; Gallo, Ryan A.; Lee, John Y.; Ivanov, Dmitry; Tse, David T.; Pelaez, Daniel
Abstract: Traumatic optic neuropathy (TON) can occur following blunt trauma to the orbit and can lead to permanent vision loss. In this study, we investigated the effectiveness of elamipretide (MTP-131), a small mitochondrially-targeted tetrapeptide, in conjunction with etanercept, a tumor necrosis factor (TNF) inhibitor, as neuroprotective agents of retinal ganglion cells (RGCs) after optic nerve trauma with sonication-induced TON (SI-TON) in mice. Treatment with intravitreal MTP-131 and subcutaneous etanercept and MTP-131 showed a 21% increase (p < 0.01) in RGC survival rate compared to PBS-treated control eyes. Subcutaneous etanercept and MTP-131 had an 11% increase (p < 0.05) in RGC survival compared to controls. Subcutaneous etanercept only group showed 20% increase (p < 0.01) in RGC survival compared to controls, while subcutaneous MTP-131 alone showed a 17% increase (p < 0.01). Surprisingly, we did not observe a synergistic effect between the two drugs in the group receiving both etanercept and MTP-131. One possible explanation for the absence of a synergistic effect is that MTP-131 and etanercept may be acting on different portions of the same pathway.